La ricerca dell’unità: idealismo ed estetica nel giovane Dewey - Cherubini, Matteo (Scenari, 2025)
The purpose of this article is to provide a comprehensive reconstruction of the intellectual and philosophical influences that shaped Dewey’s formative years (1859-1887), particularly with regard to the American romantic and Hegelian currents of his era. To this end, following a concise introduction outlining the interpretative challenge of the enduring Hegelian influence in Dewey’s philosophy, the article will proceed to examine the various stages of Dewey’s education, tracing his philosophical and personal movements between the two universities he attended (the University of Vermont and the Johns Hopkins University in Baltimore) and the encounters he had with prominent American idealists and romantics (J. Torrey, Harris, Morris). The subsequent section of the article is dedicated to an enquiry into the identification of aesthetic themes in two seminal works by Dewey: Kant and the Philosophical Method (1884) and Psychology (1887). The ultimate objective is to demonstrate how a hybrid approach to Dewey’s early work (combining historical-biographical and theoretical elements), inspired by the theory of the permanent Hegelian deposit, can generate novel possibilities for interpreting Dewey’s aesthetics.